Analisis Peran Petugas Aviation Secusity dalam Pemeriksaan Barang Bawaan Penumpang di Screening Check-Point Bandar Udara Internasional Soemarmo Boyolali - Krisnanda, Manggala Yudha Febby; Tamara, Amelia Puspa (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
This study aims to understand the role of the AVSEC unit in handling and inspecting passenger baggage that could potentially endanger flights and to identify the obstacles faced by AVSEC officers in carrying out their duties of inspecting dangerous baggage at the SCP of Adi Soemarmo International Airport, Boyolali. The research method used was a descriptive qualitative approach. Data collection was conducted through direct observation, in-depth interviews with informants from the AVSEC unit, and documentation studies, including standard operating procedures. Triangulation techniques were used to verify the validity of the data by comparing information from observations, interviews, and documentation. Results indicate that the AVSEC unit at Adi Soemarmo International Airport carries out a strategic role that includes preventive functions (preventing the entry of prohibited items), detection and identification using X-ray equipment and WTMD, enforcement of regulations in accordance with ICAO Annex 17, and providing humane service to passengers. AVSEC officers face various complex obstacles, including limited technology and equipment, limited human resources, psychological stress, high workloads, lack of structured and regular training, procedural and regulatory constraints resulting from regulatory changes without adequate socialization, and limited effective communication with passengers. It was concluded that the overall role of AVSEC at Adi Soemarmo International Airport is strategic in ensuring aviation security, but faces significant challenges in terms of technology, human resources, psychology, and procedures. Improving officer competency, modernizing equipment, and refining procedures and communications are crucial to strengthening the airport security system.